The Role of Corporate Social Responsibility and Environmental Performance on the Company's Financial Performance - Yulianti, Ani; Paramita, Ratna Wijayanti Daniar; Ana, Selvia Roos; Jualiasari, Deni; Sochib, Sochib (International Journal of Accounting and Management Research, 2025)
This research aims to test and analyze the influence of corporate social responsibility and environmental performance on the company's financial performance. This type of research is a descriptive quantitative research and uses secondary data. The population of this study is manufacturing companies that meet the requirements and operate from 2021 to 2023 The research sampling technique was carried out by purposive sampling method. The manufacturing companies that were the research sample that met the criteria amounted to 25 companies in a 3-year period. This study used multiple linear regression analysis and hypothesis testing. The results of this research hypothesis test show that corporate social responsibility has a positive effect on financial performance, where the company has managed the effectiveness of its resources well. And environmental performance also has a significant effect on the company's financial performance.